Hybrid non-destructive assessment for flow induced vibration piping systems using coupled fluid-structure interaction / Kong Keen Kuan - Kong , Keen Kuan (2020)
Pipelines and piping systems are of great importance in many industries such as water supply, petroleum and petrochemicals and nuclear power generation. They provide transport for high-velocity pressurized fluids operating under time-varying conditions. They are required to operate non-stop for a schedule of 24 hours a day, 7 days a week. Piping vibration failures have been one of the major causes of downtime, fires and explosions in industrial plant over the past 30 years. Failure of piping systems can have disastrous effects, leading to injuries and fatalities as well as to substantial cost to industry and the environment. Flow-induced vibration of the piping system is the most common causes of pipe cracking. The primary effect of flow-induced vibration is material fatigue from a large number of associated stress cycles. One of the normal ways of assessing the severity of piping vibration is to measure the associated dynamic stresses using strain gauges. However, it entails pre-determined measurement locations and depending on the complexity of the configuration, therefore this can be complicated, time-consuming, skill and experience-dependent. An alternative more objective non-destructive assessment stratagem is adopted using advanced experimental vibration analysis techniques, i.e., Operational Modal Analysis (OMA) and Operating Deflection Shape (ODS) analysis. An in-service piping system which is a highly pressurized gas transporting pipeline in an offshore platform is used as case study. An overall piping system including main pipeline and 3rd party components is investigated for problem severity identification purpose. This novel approach is complemented by Finite Element Analysis (FEA) where modal parameters such as natural frequency and mode shape extracted from OMA are used to correlate and verify the Finite Element (FE) model. Experimental based stress analysis is performed through FEA where ODS analysis result is used as initial displacement boundary condition to measure dynamic stresses. Complicated foundations involving weak joints on seams, various materials, and fracturing could be readily modelled, thus the highest stress concentration location could be identified through this method with higher accuracy. When different operating condition cases needed to be analysed and estimated, another set of experimental data have to be obtained, hence, in such situation it is time-consuming and labour intensive. The hybrid non-destructive assessment is further enhanced where the experimental based stress analysis is replaced by computational based stress analysis which utilises coupled Fluid-Structure Interaction (FSI) analysis computational mechanics. Operating parameters of the pipe, such as operating pressure, differential pressure, valve opening and flow rate are used as input for the well correlated FE model. Experimental and computational based stress analysis results in terms of vibration displacement and dynamic stress are compared. The results are in good agreement (less than 3% differences). Computational based approach is found to be more time and cost-saving where it can also be used to determine the maximum allowable operating condition for a complex piping system through examining the calculated dynamic stress of the piping system. In conclusion, the proposed hybrid non-destructive assessment is continuously enhanced in terms of time, accuracy, labour and complexity to rectify vibration-induced stress problem of in-service piping system.